CROSS-CULTURAL COMMUNICATION IN YOUTUBE ADS - Kembara, Getar; Kennedy, Janeru (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2021)
This study aims to find out how cross-cultural communication, especially Chinese culture, in the advertising video "BUKALAPAK Emang Cincai" is represented based on existing denotations, connotations and myths. Advertising is a medium that can influence the audience who watch the show. Ad makers must create creative advertisements in order to compete, so it’s no wonder the use of something different such as culture is included as an element of advertising in order to attract the interest of the audience. The language of both verbal and nonverbal from each Indonesian culture has different characteristics, one of which is Chinese culture displayed by the production team of the "Bukalapak" advertisement with the intention of increasing the audience’s knowledge about the cultural values embraced by a nation. Cultural signs are shown to have a meaning that is valuable and utilized for the benefit of the nation. To understand the meaning of signs, semiotics is one of the studies used in its analysis. The research method used is qualitative with a constructivist paradigm and the semiological analysis knife Roland Barthes, in the form of two-stage signification (two order of signification) denotation and connotation. The results of this study found that in this Bukalapak advertising video, it contains cultural elements represented through Chinese culture. Chinese culture in this advertisement is intended to promote the negotiation system as a form of appreciation for the celebration of the Chinese New Year. The culture that appears in the advertising video depicts the form of the cross-cultural communication context used into an advertisement